TINJAUAN RENCANA ANGGARAN BIAYA DAN PENJADWALAN SESUAI CONTRACT CHANGE ORDER (CCO) BERDASARKAN AHSP PUPR NO 8 TAHUN 2023 PADA PEMBANGUNAN KANTOR KEJAKSAAN NEGERI TUAL - Sarmina Palahidu; La Mohamat Saleh; Margie Civitaria Siahay (JURNAL SIMETRIK, 2026)
A construction project is a series of activities carried out to achieve development objectives within specific constraints of time, cost, and quality. During its implementation, challenges often arise in the form of work changes, which can occur in the early, middle, or late stages of the project. This study aims to identify costs in accordance with the Contract Change Order (CCO) and to plan the implementation duration for the construction of the Tual District Attorney's Office. The method used includes the Unit Price Analysis (Analisis Harga Satuan Pekerjaan/AHSP) No. 8 of 2023 for Budget Plan (RAB) calculations and the S-curve for schedule planning. The results show that the total cost of work excluding VAT is IDR 1,613,322,071.78, and the implementation period according to the CCO is 210 calendar days. Therefore, the estimated cost required for the CCO work including 11% VAT is IDR 1,790,780,000.00, with a project duration of 210 calendar days. Keywords: AHSP, CCO, Construction Project, RAB, S-Curve